Covid Crisis. Food Security And Safety In The E.U. - Robert-Adrian CANDOI-SAVU (Communications of International Proceedings, 2023)
Food security is one of the most pressing issues that mankind has faced throughout its history; it is often discussed on a global scale, while being a key issue in national security, alongside economic, financial, and demographic security. It is defined as the ability of the state and society to assure the availability of food in adequate quantity and quality for its whole people to live an active and healthy life. Food security, on the other hand, is described by the FAO as individuals having access to nutritious and safe meals at all times, which should suit both their needs and dietary preferences in order to live an active and healthy life. The purpose of this study is to examine how the COVID-19 problem has affected food security and safety, as well as to argue the necessity to secure them at the local and regional levels. The data used in the study are from FAO, Eurostat, and the Romanian National Institute of Statistics. The metrics utilized were self-sufficiency rates for the major food categories in Romania and the EU, as well as the percentage of non-regular and hired agricultural labor. Based on the findings, conclusions were reached on the impact of COVID-19 on food safety and security.
Keywords: agriculture; COVID-19; food safety; food security